2020
DOI: 10.3390/ijerph17166007
|View full text |Cite
|
Sign up to set email alerts
|

Migration Status, Internet Use, and Social Participation among Middle-Aged and Older Adults in China: Consequences for Depression

Abstract: This study aimed to examine the underlying relationship between migration status and depressive symptoms among middle-aged and older adults in China. Data were derived from three waves of panel data (2011, 2013, and 2015) from the China Health and Retirement Longitudinal Study. Two-level regression models and generalized structural equation modeling were run to fit the data. The results showed that migration status of the respondents could ameliorate their depression (β = −0.02, p < 0.01), so did internet u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 52 publications
2
26
1
Order By: Relevance
“…Research conducted by Ahn et al suggested that Internet games indirectly affected the mental health of older adults in Korea, and this influence worked through the perception of self-control [ 9 ]. Moreover, Liu et al’s study revealed that Internet use could reduce respondents’ depression via social participation [ 15 ]. Similarly, Cotton et al also found that Internet use had a positive contribution to the mental well-being of the retired older adults in the United States [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research conducted by Ahn et al suggested that Internet games indirectly affected the mental health of older adults in Korea, and this influence worked through the perception of self-control [ 9 ]. Moreover, Liu et al’s study revealed that Internet use could reduce respondents’ depression via social participation [ 15 ]. Similarly, Cotton et al also found that Internet use had a positive contribution to the mental well-being of the retired older adults in the United States [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although existing studies have analyzed the health effects of Internet use [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ], there haven’t been enough discussions focusing on the relationship between Internet use and health among older adults in China, and the conclusions of existing studies are still controversial [ 17 , 18 ]. If Internet use has an impact on the health of older adults, how does this impact happen?…”
Section: Introductionmentioning
confidence: 99%
“…One mechanism thinks that Internet use promotes health by increasing personal social interaction, leisure and entertainment, while the other believes Internet use helps users acquire health related information and resources to improve their health (Lu & Wang, 2020 ; Yang & He, 2020 ). Evidence from China suggests that Internet use can help improve both physical and mental health of the middle-aged and older adults (L. Wang, 2018 ; Wang et al, 2019a , b ; Zhao & Liu, 2020 ), because Internet use largely increases their learning behavior (Zhao & Liu, 2020 ), leisure and entertainment (L. Wang, 2018 ) and stock of social capital (Liu et al, 2020 ; Lyu & Sun, 2021 ). Evidence from other countries also shows that Internet use improves older adults’ mental health mainly by increasing their online social connections and access to health information (Cotten et al, 2012 ; Szabo et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The dependent variables were depressive symptoms measured using the 10-item Center for Epidemiologic Studies Depression Scale (CES-D-10) (36). This scale is a widely used survey tool to measure depressive symptoms among Chinese older adults, with good validity and reliability (8,27,(37)(38)(39)(40). All items are rated on a four-point scale, from "rarely" to "on some days" (1-2 days), "occasionally" (3-4 days), or "most of the time" (5-7 days).…”
Section: Measurement Of Depressive Symptomsmentioning
confidence: 99%